Wide area data replication for scientific collaborations. (21st October 2008) - Chervenak, Ann; Schuler, Robert; Kesselman, Carl; Koranda, Scott; , Brian Moe
Scientific applications require sophisticated data management capabilities. We present the Data Replication Service (DRS), one of a planned set of higher-level data management services for scientific collaborations in Grid environments. The capabilities of the DRS are based on the publication capability of the Lightweight Data Replicator (LDR) system developed for the LIGO Scientific Collaboration. We describe LIGO publication requirements and LDR functionality. We also describe the design and implementation of the DRS in the Globus Toolkit Version 4.0 environment and present performance results.